Bemba music. Extract from a lecture by Cajetan Lunsonga (Given at the Mindolo, All-African Music Conference 1965) - Lunsonga, Cajetan (International Library of African Music, 1965)
Last year I showed the sections in the music of Babemba according to the different classes of life, and how I could adapt each section into the church. This year I shall only talk about music performances in Bembaland and a little theory of how a song runs. Bemba music is not a melodious one. I mean we do not exercise melody always very much. But it is there. Bemba music is exercised mainly for two things teaching and rhythm.
Keywords: Church music; Music; Bemba (African people); Ethnomusicology; Zambia; Social Life; Social Customs; African Music